Proceedings (112) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
ProceedingsFood security in Africa: challenges, opportunities and targets for animal production is the proceedings of a conference held from 1-4 April 1996, Pretoria, South Africa edited by Dr Heinz H Meissner 409pp - ISBN 0 620 200537All Africa...